2022
DOI: 10.1002/inst.12405
|View full text |Cite
|
Sign up to set email alerts
|

DLR Institute of Systems Engineering for Future Mobility – Technical Trustworthiness as a Basis for Highly Automated and Autonomous Systems

Abstract: The newly established Institute of Systems Engineering for Future Mobility within the German Aerospace Center opened its doors at the beginning of 2022. Emerging from the former OFFIS Division Transportation after a two‐year transition phase, the new institute can draw on more than thirty years of experience in the research field of safety‐critical systems. With the transition to the DLR, the institute's new research roadmap focuses on technical trustworthiness for highly automated and autonomous systems. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Why is it widely accepted that people get their driver's license after a very limited set of driving lessons-for example, 9 h a in Germany? 2 substantial proportion of people remain very sceptical about the idea of travelling in a fully automated vehicle [3, p. 52]". In Germany, for example, around half of the participants in a quantitative market survey (n = 1000) indicated that they would not use an autonomous vehicle (e.g., for public transport) at all, or were unsure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why is it widely accepted that people get their driver's license after a very limited set of driving lessons-for example, 9 h a in Germany? 2 substantial proportion of people remain very sceptical about the idea of travelling in a fully automated vehicle [3, p. 52]". In Germany, for example, around half of the participants in a quantitative market survey (n = 1000) indicated that they would not use an autonomous vehicle (e.g., for public transport) at all, or were unsure.…”
Section: Introductionmentioning
confidence: 99%
“…Why is it widely accepted that people get their driver's license after a very limited set of driving lessons—for example, 9 ha in Germany? 2 Is it the human intelligence and the related behavior we trust in, so that the corresponding risks? The situation is quite different for trust in autonomous vehicles: Empirical studies demonstrate rather low individual trust in autonomous driving 3–7 and “indicate […] that a substantial proportion of people remain very sceptical about the idea of travelling in a fully automated vehicle [3, p. 52]”.…”
Section: Introductionmentioning
confidence: 99%